Basic consolidation and impermeability laws for nano-silica-sol grouted mudstone - Xiang, Zhe; Zhang, Nong; Pan, Dongjiang; Xie, Zhengzheng (Construction & building materials, 2023)
[Display omitted] •Revealed consolidation and anti-seepage laws in silica sol grouted mudstone.•Silica sol grout has superb injectability and permeability.•Silica sol gel is stable long-term for anti-seepage grouting.•The grouted mudstone has permeability lowered to 10-9 cm/s.•Grouting performance is compared: silica sol V.S. traditional slurries. The engineering characteristic of the water absorption, swelling, softening, and disintegration of muddy soft rocks can cause long-term large deformation and instability in muddy tunnels. Due to the poor injectability of conventional cement slurry into rock microcracks and insufficient reinforcement and anti-seepage effects on mudstone, this research performed tests on the modification and reinforcement with silica sol. Taking nano-silica sol as the research subject, this study analyzed the injectability of the slurry, the anti-seepage performance of the gel, and the macro and micro characteristics of the pore closure of consolidated mudstone. Ultimately, the basic laws of silica sol grouting and anti-seepage reinforcement for mudstone are obtained. Besides, the impact of silica sol consolidation on grouting is examined, with its performance being compared with traditional slurries. Research indicates that the silica sol slurry exhibits superior injectability and permeability, with its gel demonstrating enduring volume stability and a compact structure. When applied to mudstone, silica sol grouting markedly diminishes both porosity (by 1.68–1.88%) and permeability, reaching an ultra-low level of 10-9 cm/s. NMR tests further elucidate that silica sol is more efficacious in sealing medium and large pores (with T2 > 10 ms, >0.1 μm) compared to smaller ones (with T2 < 10 ms, below 0.1 μm). Therefore, silica sol is a prime candidate for grouting and sealing applications in micro-cracked mudstones of coal mine tunnels, particularly in muddy tunnel projects necessitating extended maintenance and anti-seepage measures. The research is expected to provide solutions to the anti-seepage and reinforcement of mudstone.